2023
DOI: 10.1371/journal.pone.0282017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of location-dependent sex difference on PD-L1, MMR/MSI, and EGFR in colorectal carcinogenesis

Abstract: Background The incidence and mortality rates of colorectal cancer (CRC) has been reported to be strongly associated to sex/gender difference. CRC shows sexual dimorphism, and sex hormones have been shown to affect the tumor immune microenvironment. This study aimed to investigate location-dependent sex differences in tumorigenic molecular characteristics in patients with colorectal tumors, including adenoma and CRC. Methods A total of 231 participants, including 138 patients with CRC, 55 patients with colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…However, studies showed that right-sided adenomas are more likely to be missed during colonoscopy [28,29]. Right-sided adenomas are also more common in women than men [30,31]. This could suggest that women have a true positive FIT but a false-negative colonoscopy with missed findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies showed that right-sided adenomas are more likely to be missed during colonoscopy [28,29]. Right-sided adenomas are also more common in women than men [30,31]. This could suggest that women have a true positive FIT but a false-negative colonoscopy with missed findings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in recent study in Japan reported that serrated adenoma/polyp (SSA/P) lesions were mostly located in the proximal colon, and SSA/P with dysplasia or invasive carcinoma was more associated with female sex compared with SSA/P without dysplasia [ 152 ]. Furthermore, a recent study in Korea also exhibited the molecular differences such as programmed cell death-ligand 1 (PD-L1), MMR/MSI status and EGFR expression in CRC according to sex and tumor location that females with proximal CRC showed a markedly higher incidence of dMMR/MSI-high status, suggesting a possible underlying mechanism of sex-specific colorectal carcinogenesis [ 153 ]. From these results, the association with SSA/P with dysplasia or invasive carcinoma in proximal colon and female sex is suggested, and additional research focusing on sex differences in molecular pathways is needed.…”
Section: Sex Differences In Pathogenesismentioning
confidence: 99%
“…A point mutation (V600E) in the BRAF oncogene is known to be mutually exclusive with mutation in KRAS [ 164 ] and associated with a poor prognosis in metastatic [ 165 ] and node-positive CRCs [ 153 159 162 ], shows sex difference. First, sessile SSA/Ps, early precursor lesions in the serrated neoplasia pathway and results in BRAF-mutated CRCs, are known to be associated with advanced age, female sex, and proximal colon [ 152 ].…”
Section: Sex Differences In Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations